Analisis Kebijakan Zonasi Terhadap Masyarakat Kurang Mampu: Halangan dan Solusi - Aditya Priyandika; Sri Roekminiati; Dandy Patrija Wirawan (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Education is a fundamental right of every citizen that the state is obliged to guarantee, particularly for underprivileged communities. The zoning policy in the New Student Admission System (SPMB) was introduced as an effort to equalize access to education in Indonesia. This study aims to evaluate the implementation of the zoning policy and educational assistance programs such as PIP and PKH for underprivileged communities in Sidoarjo Regency using an ex ante evaluative approach with a qualitative library research method. The evaluation was conducted based on six criteria by William N. Dunn, namely effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The results indicate that the effectiveness, efficiency, and equity criteria performed relatively well, where the affirmation pathway met the 15% quota, PIP funds were distributed without waste, and various SPMB pathways provided proportional benefits. However, adequacy and responsiveness emerged as the main weaknesses, marked by 72 school dropout cases, low utilization of funds for educational purposes, and insufficient program socialization to parents. Regular face-to-face socialization, active mentoring, and cross-sector coordination are needed to optimize the zoning policy for underprivileged communities.